The cost-effectiveness profile of sex-neutral HPV immunisation in European tender-based settings: a model-based assessment - Venetia Qendri, MSc; Johannes A Bogaards, PhD; Iacopo Baussano, MD; Fulvio Lazzarato, PhD; Simopekka Vänskä, PhD; Johannes Berkhof, ProfPhD (The Lancet Public Health, 2020)
Summary: Background: In many European countries, human papillomavirus (HPV) vaccine uptake among girls has remained below target levels, supporting the scope for vaccination of boys. We aimed to investigate if sex-neutral HPV vaccination can be considered cost-effective compared with girls-only vaccination at uptake levels equal to those among girls and under tender-based vaccination costs achieved throughout Europe. Methods: We investigated the cost-effectiveness of sex-neutral HPV vaccination in European tender-based settings. We applied a Bayesian synthesis framework for health economic evaluation to 11 countries (Austria, Belgium, Croatia, Estonia, Italy, Latvia, the Netherlands, Poland, Slovenia, Spain, and Sweden), accommodating country-specific information on key epidemiological and economic parameters, and on current HPV vaccination programmes. We used projections from three independently developed HPV transmission models to tailor region-specific herd effects. The main outcome measures in the comparison of sex-neutral with girls-only vaccination were cancer cases prevented and incremental cost-effectiveness ratios (ICERs), defined as the cost in international dollars (I$) per life-year gained. Findings: The total number of cancer cases to be prevented by vaccinating girls at currently realised vaccine uptake varied from 318 (95% CI 197–405) per cohort of 200 000 preadolescents (100 000 girls plus 100 000 boys) in Croatia (under 20% uptake of the 9-valent vaccine) to 1904 (1741–2101) in Estonia (under 70% uptake of the 9-valent vaccine). Vaccinating boys at equal coverage increased these respective numbers by 168 (95% CI 121–213) in Croatia and 467 (391–587) in Estonia. Sex-neutral vaccination was likely to be cost-effective, with ICERs of sex-neutral compared with girls-only vaccination varying from I$4300 per life-year gained in Latvia (95% credibility interval 3450–5160; 40% uptake) to I$25 720 per life-year gained in Spain (21 380–30 330; 80% uptake). At uniform 80% uptake, a favourable cost-effectiveness profile was retained for most of the countries investigated (Austria, Belgium, Italy, Latvia, the Netherlands, Slovenia, Spain, and Sweden). Interpretation: Sex-neutral HPV vaccination is economically attractive in European tender-based settings. However, tendering mechanisms need to ensure that vaccination of boys will remain cost-effective at high vaccine uptake rates. Funding: European Commission 7th Framework Programme and WHO.